How crises work: A model of error cause and effect in surgical practice. (August 2022) - Gogalniceanu, Petrut; Karydis, Nikolaos; Kessaris, Nicos; Olsburgh, Jonathon; Calder, Francis; Sevdalis, Nick; Mamode, Nizam
Abstract: Introduction: Surgical crises have major consequences for patients, staff and healthcare institutions. Nevertheless, their aetiology and evolution are poorly understood outside the remit of root-cause analyses. Aims: To develop a crisis model in surgery in order to aid the reporting and management of safety critical events. Methods: A narrative review surveyed the safety literature on failure causes, mechanisms and effects in the context of surgical crises. Sources were identified using non-probability sampling, with selection and inclusion being determined by author panel consensus. The data underwent thematic analysis and reporting followed the recommendation of the SALSA framework. Results: Data from 133 sources derived five principal themes. Analysis suggested that surgical care processes become destabilized in a step-wise manner. This crisis chain is initiated by four categories of threat or risk: (i) the systems in which surgeons operate; (ii) surgeons' technical, cognitive and behavioural skills ; (iii) surgeons' physiological and psychological state ( operational condition ); and (iv) professional culture . Once triggered, the crisis chain is driven by only three types of errors: Type I. Performance errors consist of failures to diagnose, plan or execute tasks; Type II. Awareness errors are failures to recognise, comprehend or extrapolate the impact of performance failures; Type III. Rescue errors represent failures to correct faulty performance. The co-occurrence of all three error types gives rise to harm, which can lead to a crisis in the absence of mitigating actions. Conclusion: Surgical crises may be triggered by four categories of threat and driven by only three types of error. These may represent universal targets for safety interventions that create new opportunities for crisis management. Graphical abstract: Image 1 Highlights: Surgical crises evolve sequentially, as a result of growing instability within a clinical care process Crises are driven by three error types: 1. performance failures; 2. monitoring and awareness failures; 3. rescue failures Errors arise from 4 threat domains: 1. operators' skills; 2. operators' condition; 3. professional culture; 4. healthcare systems Understanding the key checkpoints in the crisis chain creates universal targets for crisis management interventions